Prevalence of Frank's sign in healthy young individuals, morphological characteristics, and its association with family history of chronic disease - Aksu, Feyza; Akkoc, Ramazan Fazil (Humana Press Inc, 2024)
Frank's sign (FS, earlobe crease) is known to be associated with many chronic diseases i.e. coronary, cerebrovascular, and peripheral vascular diseases. The objective of this study is to investigate the presence and grade of FS in healthy, young-adult individuals aging between 18 and 25. Furthermore, to evaluate the relationship between FS and the chronic disease history of first-degree family members. 853 healthy people with a mean age of 20.09 years were imvolved in the research on a voluntary basis. Of 853 individuals, 85.3% (n:728) had no FS, whereas 14.7% (n:125) had. Of the 125 people observed FS, 41.6% (n:52) were female and 58.4% (n:73) were male. Of the 125 people diagnosed with FS, 32.8% (n:41) had no family history of any chronic disease, and 67.2% (n:84) had at least 1 family history of chronic disease as well. It was determined that there was a statistically significant (p < 0.05) relationship between FS identified in healthy individuals and familial chronic disease history. In this study, while no FS was observed in 85.3% of the participants, grade 1 was detected in 12.4% (n:105), grade 2a in 1.9% (n:16), grade 2b in 0.2% (n:2), and grade 3 in 0.2% (n:2). To the best of our knowledge, this study investigated the relationship between the presence and grade of FS in the healthy, young, Turkish population and the presence/absence of chronic disease in the first-degree relatives of individuals for the very first time. As a result of larger studies, being aware of the presence of FS, especially in young healthy individuals, may help predict some chronic diseases, and caution may be taken to avoid these diseases at an early age in at-risk individuals.
Keywords: Frank's sign (FS); Earlobe crease (ELC); Preventive medicine; Morphology